Active citizenship by active learning - Ahrari, Seyedali; Othman, Jamilah; Hassan, Md. Salleh; Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva (Asian Network for Scientific Information, 2014)
Active citizenship is a way of development greater young citizen responsibility. It is a combination of obligations and responsibilities through involvement in civic issues. Be an active citizen need new ways of educating students which are different from traditional learning methods. Active learning method derived from learned-centred approaches stress more on students as intelligent entities rather than just receivers. Employing methods of active learning in citizenship education has some obstacles but the advantages are greater than passive ways of learning.